Karakteristik Dan Struktur Kesempatan Kerja Di Kabupaten Kutai Kartanegara - H. Syaukani HR (Universitas Islam Indonesia, 2003)
This shift in employment has result from changes accurring in the economic structure. High growt in the industrial sektor, particularly in manufacturing and construc¬tion, has created many job opportunities in these sektor. On the contranry, the shift in the use of land from primer to other purposes has defresed employment opportunities in the primer sektor. Furthermore, people perceive that working in the tertier sektor provides better incen¬tive than working in the primer sektor.Kaywords: production, employment, economic growt.